Battery separator and method of manufacturing the same

CN122893201APending Publication Date: 2026-10-09ZNL ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580019834.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-08
Filing Date
2025-03-05
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,由于其刚度,难以将其加工成薄膜

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122893201A_ABST
    Figure CN122893201A_ABST
Patent Text Reader

Abstract

A solid-state separator for a battery, comprising: - a first layer comprising a pre-lithiated or pre-sodiated polyphenylene sulfide (PPS) cellulose nanofiber (CelNF) composite self-supporting membrane; - a second layer comprising a porous polyolefin membrane; and, - a third layer comprising a ceramic nanolayer disposed between the first and second layers. Also disclosed are batteries comprising such separators and methods and systems for producing them.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a solid-state separator for batteries. More specifically, this invention relates to a solid-state separator comprising a pre-lithiated or pre-sodium-treated polyphenylene sulfide (PPS) cellulose nanofiber composite self-supporting membrane, and a battery comprising such a separator. This invention also relates to systems and methods for producing PPS cellulose nanofiber composite self-supporting membranes. Background Technology

[0002] The development of advanced separators is key to significantly improving battery safety. Separators act as critical components within metal-ion batteries (such as lithium (Li), sodium (Na), and zinc (Zn) batteries), preventing physical contact between the anode and cathode, which can lead to short circuits and thermal runaway. Innovations in separator technology, such as improving thermal stability, enhancing electrolyte compatibility, and incorporating flame-retardant materials, are crucial in reducing the risk of battery failure. By focusing on advancing safer and more reliable separators, the battery industry can address the inherent safety issues of lithium-ion and sodium-ion batteries, paving the way for their wider and safer application across various sectors, including consumer electronics and electric vehicles.

[0003] Solid-state separators are crucial for the safety, efficiency, and performance of Li and Na-ion batteries. Initially, these batteries used porous polymers such as polyethylene and polypropylene as separators. These separators were chosen because they could achieve ion conductivity through pores filled with electrolyte and maintain a physical barrier between the anode and cathode, thus preventing short circuits. However, these porous separators have significant problems. They can lead to uneven lithium-ion transport and generate localized electric fields, which may promote the formation of lithium dendrites, particularly around the pores. Additionally, their tendency to shrink at high temperatures can lead to short circuits, and their structural integrity is at risk of being compromised by punctures.

[0004] Overcoming the limitations of traditional porous separators, there is a significant trend towards developing non-porous solid-state separators for lithium-ion batteries. Unlike their microporous counterparts, non-porous separators have no pores or openings in their structure. This design helps suppress the formation of lithium dendrites (sharp, needle-like protrusions that can appear on lithium metal anodes). These dendrites pose significant risks, including potential short circuits and safety hazards. Furthermore, their robust structure makes the battery more resistant to physical damage. By integrating non-porous separators, the capacity and energy density of lithium-ion batteries can be improved. This improvement is particularly beneficial for devices using lithium metal anodes, including wearable technologies, drones, and electric vehicles, where performance and safety are paramount. These advanced separators offer improved thermal stability and mechanical strength at high temperatures, greatly enhancing battery safety.

[0005] However, the transition to non-porous materials presents several challenges, including developing new solid-state electrolytes that can conduct lithium ions without liquid electrolytes and ensuring scalability for large-scale production. These materials must possess high ionic conductivity, electrochemical stability, and compatibility with electrode materials. Furthermore, adapting manufacturing processes to accommodate these new materials and ensuring scalability for large-scale production are crucial steps for the widespread adoption of non-porous separators in lithium-ion batteries.

[0006] The transition to non-porous materials for lithium-ion batteries involves a series of complex challenges. A key element is the innovation of new solid-state electrolytes that facilitate lithium-ion movement without the need for traditional liquid electrolytes. These novel materials must exhibit excellent ionic conductivity, maintain electrochemical stability, and be fully compatible with existing electrode materials. Furthermore, manufacturing processes must be developed to effectively integrate these advanced materials, ensuring their mass production capability. Achieving scalability for large-scale production is crucial for the widespread implementation of non-porous separators in the Li-ion and Na-ion battery industries.

[0007] Solid-state membranes made from pre-lithiated polyphenylene sulfide (PPS) have shown promising properties, such as high Li-ion conductivity, high thermal stability, and high chemical resistance (US2022037696). This is because PPS is a high-performance thermoplastic polymer known for its excellent heat resistance, chemical and corrosion resistance, as well as its rigidity and dimensional stability. However, its rigidity makes it difficult to process into thin films. Thin films have relatively low mechanical strength and require mechanical reinforcement.

[0008] As research in this field continues to advance, the development of non-porous solid-state separators is expected to significantly improve the safety, capacity, and overall performance of Li-ion and Na-ion batteries. This progress is expected to open up new possibilities for their applications, ranging from consumer electronics to electric vehicles and energy storage solutions, marking a major leap forward in battery technology. Summary of the Invention

[0009] The purpose of this invention is to improve or reduce at least one of the disadvantages of the prior art, or at least to provide a useful alternative to the prior art.

[0010] This objective is achieved by the features specified in the following description and appended claims.

[0011] This invention is defined by the independent claims. The dependent claims define advantageous embodiments of the invention. Attached Figure Description

[0012] Figure 1 An illustrative system according to the sixth aspect of the invention is shown. Detailed Implementation

[0013] In a first aspect, the present invention relates to a solid-state separator for a battery, the solid-state separator comprising: - The first layer comprises a pre-lithiated or pre-sodium-lithiated polyphenylene sulfide (PPS) cellulose nanofiber (CelNF) composite (PPSCC) self-supporting membrane. - The second layer comprises a porous polyolefin membrane; and, - The third layer includes a ceramic nanolayer disposed between the first and second layers.

[0014] In one embodiment, the second layer may include polyethylene (PE) or polypropylene (PP). Both PE and PP have shown potential for use in preventing thermal runaway, enhancing mechanical strength, and suppressing reduction and oxidation of the first layer of the solid-state battery separator.

[0015] The thickness of the second layer can be in the range of 5-20 μm, preferably 5-10 μm. Thin layers are desirable for maintaining high energy density in the battery, while thicker layers are desirable for enhanced mechanical stability. 5-20 μm, and especially 5-10 μm, has been found to be the optimal trade-off for certain applications.

[0016] In one embodiment, the first layer may comprise PPS, CelNF, and polytetrafluoroethylene (PTFE) powder in a weight ratio of 89-97%:0.1-5%:3-8%, preferably 90-94%:1-3%:4-6%. The small fraction of well-dispersed CelNF maintains the fiber network threshold in the membrane, enhancing mechanical properties and Li ion transport without creating excessive pores in the solid membrane. In addition to the small fraction of PTFE, the fiber structure contributes to processability for producing self-supporting membranes without compromising the ion transport properties of the PPS membrane.

[0017] In one embodiment, the thickness of the ceramic nanolayer can be in the range of 30-300 nm.

[0018] The thickness of the first layer can be 5-45 μm, preferably 10-30 μm, or even more preferably 15-25 μm.

[0019] In one embodiment, the porosity of the first layer may be less than 10%, preferably less than 3%. The porosity can be measured by N2 or CO2 adsorption.

[0020] The third layer may include one or more of the following: - Aluminum oxide; -Li-rich ceramics, such as Li salts, Li-rich cathode materials, lithium phosphorus oxynitride (LiPON), or lithium titanate; and, - Highly porous materials, such as carbon nanospheres or metal-organic framework (MOF) materials.

[0021] The thickness of the separator can be in the range of 10-60 μm, preferably 15-30 μm, and even more preferably 20-25 μm. For the first layer, the total thickness of the separator is a trade-off between the energy density of the battery using the separator and its mechanical stability.

[0022] In one embodiment, the width of the solid diaphragm can be in the range of 5-160 cm, wherein the upper end of the range can correspond to the width in industrial-scale processes, and the lower end of the range can correspond to the typical width in laboratory-scale processes.

[0023] To address the challenges of previous methods, this invention introduces a solid-state separator designed to significantly improve battery performance. The invention provides a multifunctional solid-state separator for batteries (e.g., Li-ion or Na-ion batteries) comprising a multilayer structure. The top layer is a self-supporting membrane of PPS-cellulose nanofiber composite material, and the bottom layer is a porous polyolefin (e.g., PE) layer. A ceramic nanolayer is provided between the two layers. The solid-state separator according to a first aspect of the invention exhibits excellent mechanical strength, while its manufacturing method is significantly simplified.

[0024] This design ensures excellent compatibility and wettability with the electrolyte, promoting efficient ion transport. Additionally, the membrane possesses excellent thermal properties; the high melting point of PPS (280-285°C) contributes to its robust and stable performance. This characteristic, combined with the material's ability to prevent thermal runaway, significantly enhances battery safety. This non-porous PPSCC membrane, the first layer, is designed to selectively allow either lithium or sodium ions to pass through, thereby reducing dendrite growth. It achieves this by promoting uniform ion diffusion and eliminating any pores, which effectively prevents the formation of lithium dendrites. The composite membrane is prepared from a blend of pre-lithiated polyphenylene sulfide (PPS) powder, cellulose fiber (CelNF), and polytetrafluoroethylene (PTFE) powder, forming a thin solid membrane separator. As described below, the production method involves orienting and heating the mixture of pre-lithiated or pre-sodiumized PPS powder, cellulose fiber, and PTFE in an ultrasonic drying gas stream, followed by pressing it into a self-supporting membrane with precisely controlled thickness. In this process, PTFE is converted into fibers, and a small amount of cellulose nanofibers (0.01 to 3% by weight) is incorporated into the composite material. This addition not only enhances the thermal elongation properties of the thermoplastic PPS powder but also significantly improves the mechanical strength of the self-supporting membrane, thereby improving the controllability of the automated manufacturing process.

[0025] This disclosure relates to the versatility of PPSCC membranes. A multilayer design comprises thin, porous layers of polyolefin, polyethylene (PE), or polypropylene (PP) layers, typically 3-10 micrometers thick. It provides protection against thermal runaway: in overheating conditions, as the temperature rises, the pores close and ion transport is effectively shut off until the PE layer melts at approximately 105°C-130°C and the PP layer melts at 130°C-170°C. Furthermore, the PPSCC membrane exhibits excellent thermal stability and maintains superior dimensional stability up to 280°C, preventing direct contact between the anode and cathode, thereby significantly reducing the risk of a short circuit. According to UL94 standards, PPS exhibits a low flammability rate, achieving a V-0 rating. This indicates a high level of fire resistance, providing additional safety features. This design prevents the battery from reaching the thermal runaway threshold and potentially generating a flame, thus enhancing safety.

[0026] This disclosure achieves the versatility of PPSCC films by designing a coating (i.e., a third layer between the first and second layers) between the PPSCC and the polyolefin layer. The coating can include, for example, alumina, Li-rich ceramics [such as Li salts, Li-rich cathode materials, lithium phosphorus oxynitride (LiPON), and lithium titanate], highly porous materials (such as carbon nanospheres and MOF materials). A solution containing the above materials is used as an adhesive to laminate the polyolefin and PPSCC layers onto each other. The third layer, formed after drying, increases the dimensional stability of the polyolefin layer. The third layer may include alumina and / or lithium-rich materials or compounds (e.g., Li salts, Li-rich cathode materials, lithium phosphorus oxynitride (LiPON), lithium titanate) to provide Li replenishment. In lithium batteries, particularly lithium-ion batteries, additional lithium is sometimes introduced to compensate for lithium loss during the initial charging period and to enhance overall battery performance. MOF materials and / or carbon nanospheres can also be used in the coating and can increase electrolyte retention and improve compatibility with the electrodes.

[0027] In a second aspect, the present invention relates to a battery comprising a solid separator according to a first aspect of the present invention.

[0028] In one implementation, the battery can be a Li battery or a Na battery.

[0029] In a third aspect, the present invention relates to a method for producing a self-supporting, pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite membrane (PPSCC), the method comprising the following steps: - Mix and grind metal chloride, tetrachloro-p-benzoquinone (TCBQ) and PPS powder dissolved in deionized water to form a mixed slurry; - Transfer the mixed slurry to a reactor for hydrothermal treatment; - The hydrothermally treated mixture is washed and filtered in a centrifuge; - Dry the filtered solution to break down the PPS powder; - At a temperature in which the PTFE powder is in a glassy state, the decomposed PPS powder is mixed with cellulose fibers and polytetrafluoroethylene (PTFE) powder to obtain a mixed solution; - Grind the mixed solution in dry compressed air; - A film is obtained by compacting and grinding a mixture using one or more rollers; - Pass the membrane through a hot calender to obtain a self-supporting pre-lithiated polyphenylene sulfide (PPS) cellulose nanofiber composite membrane.

[0030] In a fourth aspect, the present invention relates to a method for preparing a self-supporting pre-lithiated polyphenylene sulfide (PPS) cellulose nanofiber composite membrane, the method comprising the following steps: - Metal chloride, tetrachloro-p-benzoquinone (TCBQ), polyphenylene sulfide (PPS) powder and cellulose fiber dissolved in deionized water are mixed and ground to form a mixed slurry; - The mixed slurry is transferred to a reactor for hydrothermal treatment; - The hydrothermally treated mixture is washed and filtered in a centrifuge; - Dry the filtered solution to break down the PPS powder; - At a temperature in which the PTFE powder is in a glassy state, the decomposed PPS powder is mixed with polytetrafluoroethylene (PTFE) powder to obtain a mixed solution; - Grind the mixed solution in dry compressed air; - A film is obtained by compacting and grinding a mixture using one or more rollers; - Pass the membrane through a hot calender to obtain a self-supporting pre-lithiated polyphenylene sulfide (PPS) cellulose nanofiber composite membrane.

[0031] In one embodiment, the metal chloride may be one or more of the following: - Lithium chloride; - Sodium chloride; -Magnesium chloride; and, Aluminum chloride.

[0032] In one embodiment, the PPS powder may be a semi-crystalline PPS powder with linear chains and terminal crosslinks, having a crystallinity >60% in the range of 1-25 μm, preferably 1-5 μm.

[0033] The mass ratio of metal chlorides, DIW, and TCBQ to the total PPS mass can be approximately 1:30:5:100.

[0034] In one embodiment, the hydrothermal treatment can be carried out at a reaction temperature of about 210°C for 1-3 hours, preferably about 2 hours, with a vapor pressure of 60-70 bar.

[0035] In one embodiment, the mixing of PPS powder with cellulose fibers and PTFE can be carried out at a temperature of 45-50°C.

[0036] In one embodiment, grinding can be carried out in an air jet mill preheated to a temperature of 40-50°C by compressed air.

[0037] The step of compacting the milled mixture with one or more rollers may include producing a film with a thickness of 1.0-3.0 mm, preferably 1.0-1.5 mm. In one embodiment, the method may further include the step of passing the film through a hot calender, including a step of cold rolling the film at a roller temperature of about 40-70°C, preferably 45-55°C, to obtain a film with a thickness of 0.3-0.5 mm.

[0038] In one embodiment, the roll temperature of the hot calender can be 125-130°C.

[0039] The friction of the roller can be in the range of 1%-20%, preferably in the range of 8%-12%.

[0040] The line load can be in the range of 500-250 N / mm, preferably in the range of 350-370 N / mm.

[0041] When the process is scaled up to an industrial scale, the speed can preferably be 100 m / min or higher. Although the experiments given below were primarily conducted in a controlled, small-scale setting, the speed and line load / roller pressure can be increased without significantly affecting the parameters of the preceding steps of the method.

[0042] In a fifth aspect, the present invention relates to a method for preparing a self-supporting pre-lithiated polyphenylene sulfide (PPS) cellulose nanofiber composite membrane according to a method of a third or fourth aspect of the present invention, the method further comprising the following steps: - A porous polyolefin membrane is laminated onto a PPS cellulose nanofiber membrane using an adhesive containing a ceramic nanolayer.

[0043] In a sixth aspect, the present invention relates to a system for carrying out a method according to a third, fourth, or fifth aspect of the invention, the system comprising: - Main storage tank for metal chlorides, deionized water, tetrachloro-p-benzoquinone (TCBQ), PPS powder and optional cellulose fibers; - First mixer, used to mix the contents of future autonomous storage tanks into a mixed slurry; - Reactor for hydrothermal treatment of mixed slurries; - Centrifuges are used for washing and filtering slurries from hydrothermal treatment; - An apparatus for drying and filtering a solution to break down PPS powder; A secondary storage tank for the decomposition of PPS powder, polytetrafluoroethylene (PTFE) powder, and optional cellulose nanofibers (if not included in the main storage tank). - A second mixer for mixing the contents from the secondary storage tank; - A grinder, used to grind mixed solutions in compressed air; - One or more pairs of rollers are used to compact the grinding solution into a film; - A hot calender is used to pass the compacted film through the machine to obtain a self-supporting, pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite film; and optionally, - A laminator is used to add porous polyolefin membranes to self-supporting pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite membranes via ceramic nanolayer adhesives to obtain solid-state battery separators.

[0044] The following is an exemplary embodiment of a method according to a third aspect of the present invention, which employs a continuous manufacturing process for the mass production of the PPSCC layer of the solid separator disclosed herein. This exemplary process includes several stages: a) Mix the powders to obtain a homogeneous mixture; b) Pre-treat the mixed powder in an autoclave reactor to prepare for subsequent stages; c) Use a centrifuge to filter the pretreated mixed powder to separate and purify the components; d) Dry the filtered mixed powder in a fluidized bed reactor to obtain the optimal moisture content; e) Finally, the pretreated polyphenylene sulfide (PPS) powder is thoroughly mixed with cellulose nanofibers and polytetrafluoroethylene (PTFE) powder to ensure uniform distribution; f) Preheated compressed air is used to feed the final mixed solution into a high-speed shearing machine, where the airflow rate reaches supersonic speeds to fiberize the powder; g) The fibrous powder is extruded through a roller press to form granules.

[0045] h) The pellets are processed by an automated multi-roller machine involving continuous cold and hot calendering / rolling steps to complete the self-supporting PPSCC film.

[0046] The result of this exemplary method is a virtually defect-free self-supporting membrane with a thickness ranging from 5 to 45 μm, typically 10 to 30 μm, and a width between 5 and 160 cm. This innovative manufacturing method ensures high-quality, consistent production of solid-state membranes suitable for large-scale applications.

[0047] As used herein, the terms “lithium battery” and “sodium battery” refer to all types of Li and Na batteries known, but not limited to, rechargeable or secondary Li-ion, Na-ion and Zn-ion batteries, metal batteries, etc.

[0048] Examples of embodiments shown in the accompanying drawings are described below, wherein: Any location indication refers to the location shown in the diagram.

[0049] In the accompanying drawings, the same or corresponding elements are indicated by the same reference numerals. For clarity, some elements may not have reference numerals in some drawings.

[0050] Figure 1 An exemplary and highly illustrative system 1 according to a sixth aspect of the invention is shown. The system 1 shown is adapted to produce a solid membrane according to a first aspect of the invention by means of methods according to the fourth and fifth aspects of the invention.

[0051] Multiple storage tanks / dispensing compartments are provided, wherein the first storage tank 2 contains pre-lithiated PPS powder, the second storage tank 4 contains tetrachloro-p-benzoquinone (TCBQ), the third storage tank 6 contains metal chloride (xCl), the fourth storage tank 8 contains deionized water (DIW), and the fifth storage tank 10 contains cellulose nanofibers (CelNF). It should be noted that in this specific embodiment, CelNF is added and mixed into the solution from the outset, rather than being added and mixed into the solution in a later fibrillation step.

[0052] One or more first distribution pumps 12 are provided to distribute the contents from the respective tanks 2-10 in the desired amount into a first resonant acoustic mixer (RAM) 14 (with abrasive media not shown). In some embodiments, the abrasive media may be Teflon-coated balls, such as steel balls or ceramic balls. A first RAM distribution pump 15 is provided to move the mixed slurry from RAM 14 into a closed reactor 16 (in the form of an autoclave) for hydrothermal treatment. The autoclave 16 is provided with means (not shown) for controlling feed and discharge. The mixed slurry is further conveyed from the autoclave 16 to a scraper centrifuge 18 via an autoclave distribution pump 17. In the scraper centrifuge 18, the slurry is washed to a neutral pH and filtered into a "filter cake". The filter cake is transferred to a fluidized bed reactor 22 by a centrifugal distribution pump 20 to break down the aggregated particles, now in the form of PPS powder with CelNF. The PPS powder with CelNF is fed into a sixth storage tank 26 by a fluidized bed distribution pump 24, where it is mixed with xCl. The seventh storage tank 28 contains PTFE powder. The contents from the sixth storage tank 26 and the seventh storage tank 28 are drawn into the second RAM 33 via cold chamber distribution pumps 30 and 32, respectively. The second RAM 33, the sixth storage tank 26, the seventh storage tank 28, and the cold chamber distribution pumps 30 and 32 are located in the cold chamber 34, which means that the PTFE powder is in a glassy state.

[0053] The mixed solution from the second RAM 33, together with compressed air from the rotary screw air compressor 38, is fed into the jet mill 36 via the second RAM distribution pump 37. The air is pharmaceutical-grade dry compressed air according to standard ISO 8573-1 and 1-2-1 (particle-water-oil). The rotary screw air compressor 38 receives air from the fluidized bed reactor via a cooler 40. During air jet milling, the size of the PPS powder particles decreases due to the combination of grinding and shearing forces, thereby causing the PTFE molecular chains to extend and open to form fibers. The PTFE fibers form a network-like bonded structure on the surface of the PPS particles, giving them a marshmallow-like powder appearance. The marshmallow-like powder is collected through a gas filter.

[0054] Powder from the air jet mill 36 is distributed to a screw feeder unit 44 via an air jet mill distribution pump 42. The screw feeder unit 44 feeds the powder (now in strip / ribbon form) at room temperature into a series of vertically spaced, controlled-gap cooling rollers. In the illustrated embodiment, this series includes three parallel-operating main roller pairs 46, which feed the resulting film 50 to secondary roller pairs 48, producing a film with a thickness of approximately 1 mm. The resulting relatively thick film is then passed through multiple horizontally arranged rollers 52 at a temperature of approximately 50°C, with the gap between the rollers gradually decreasing. The resulting film after passing through the horizontal rollers has a thickness of approximately 0.5 mm and is substantially free of defects.

[0055] Following the horizontal roller 52, the film 50 is conveyed to a hot calender 54 at approximately 130°C. The pressure between the rollers 56 of the calender 56 is set to 45 kN, corresponding to a linear load of 360 N / mm. The friction between the rollers 56 is 10%, and the speed is 2.5 m / min. Friction is defined as friction in the roller bearings and can be controlled by individually controlling the speed of the rollers 56.

[0056] Then, before applying the ceramic nanolayer adhesive stored in the eighth tank 58 onto the membrane in the coating machine 60, the final PPSCC membrane 50 is trimmed in the trimmer 57. Adhesive is dispensed from the eighth tank 58 via the adhesive dispensing pump 62. The membrane 50 with adhesive is then laminated onto a PE / PP membrane 64 in the laminator 66. The PE / PP membrane 64 is stored on a reel 68. The resulting membrane 3 is passed through the slitting device 70 before being stored on a storage reel 72 at its desired length and width.

[0057] This process is executed and controlled by control unit 74.

[0058] Other embodiments and reference embodiments of the method according to the invention are given below. In particular, embodiments 1, 3 and 7-8 correspond to the method according to various aspects of the invention, while embodiments 2, 4-6 and 9 are included for reference.

[0059] Example 1 This embodiment provides a method for manufacturing a multifunctional solid-state Li battery separator, which includes the following steps: (1) Powder mixture Metal chloride (xCl), tetrachloro-p-benzoquinone (TCBQ), and polyphenylene sulfide (PPS) powder dissolved in deionized water (DIW) were mixed and ground in a resonant acoustic mixer with grinding media. The mixture was then transferred to a closed reactor for hydrothermal reaction. After the reaction, the powder was washed to neutral pH and filtered in a vertical scraper centrifuge. The filter cake was dried in a fluidized bed dryer to decompose agglomerated particles, yielding PPS powder.

[0060] (2) fibrillation Pre-lithiated PPS powder, CelNF, and PTFE powder are uniformly mixed in a resonant acoustic mixer at a weight percentage of 91%:3%:6% without applying shear force to the powders, and the mixing process is carried out at a temperature under which the polytetrafluoroethylene is in a glassy state.

[0061] Preheated pharmaceutical-grade dry compressed air from a rotary screw air compressor, conforming to ISO 8573-1 and 1-2-1 grade (particle-water-oil), is injected into the spiral air jet mill.

[0062] Powder is introduced into the grinding chamber of an air jet mill via a feeder containing high-speed, dry compressed air. During air jet milling, the size of the PPS powder particles decreases due to the combination of grinding and shearing forces, while the PTFE molecular chains extend and open to form fibers. The PTFE fibers form a network structure on the surface of the PPS particles, giving them a marshmallow-like powder appearance. The marshmallow-like powder is collected through a gas filter.

[0063] (3) Film Forming The powder is then fed into a roller precompactor via a feeding mechanism to produce strips or belts. These strips or belts are then fed directly at room temperature into multiple consecutive, vertically automated gap-controlled cold rollers to produce films with a thickness of 1.0 mm to 1.5 mm.

[0064] The resulting thick film was then passed through multiple horizontal rollers controlled by automatic constant force and speed, with a friction of 15% and a temperature of 50°C. The gaps between the rollers were 1000, 900, 700, 600, and 500 μm, respectively. The final defect-free film thickness was 520 μm.

[0065] The resulting film is subjected to hot horizontal calendering, which is controlled by constant force and constant speed at a temperature of 130°C and 10% friction. The thickness of the film after hot calendering is 15 μm. This thickness is obtained under a roll pressure of 45 kN, a corresponding linear load of 360 N / mm width, and a speed of 2.5 m / min. When scaling up production, higher speeds should be used, such as approximately 100 m / min or even higher.

[0066] The produced diaphragm is then cut to the desired width, and the outer edge is cut off to prepare a diaphragm including a PPS layer with cellulose nanofibers.

[0067] (4) PE layer lamination To prepare a solid-state separator for Li and Na batteries, a polyolefin layer is attached to the PPS layer to prevent thermal runaway and enhance mechanical strength.

[0068] A PE or PP layer is laminated onto one side of the PPS layer to increase the mechanical strength of the solid membrane. The PE or PP layer is then adhered to the PPS using a ceramic adhesive containing alumina colloid. Finally, the laminate is dried in air at 120°C. The ceramic adhesive transforms into an Al2O3 coating.

[0069] The conductivity of lithium ions was determined using an electrochemical method with a multichannel constant potentiometer (PARSTAT MC, AMETEK). The measured lithium-ion conductivity was 2.5 × 10⁻⁶. -4 S / cm 2 The tensile strength of the membrane was evaluated according to the ASTM D882 standard test method, and the measured tensile strength was 19.4 MPa.

[0070] The thermal stability of the multilayer film was tested at 130°C. The PE layer melted, but the PPS layer maintained its original dimensions, demonstrating its ability to prevent thermal runaway and thus improve the safety of solid-state batteries.

[0071] The porosity, measured by N2 adsorption, was 3%. The membrane's gas tightness was measured using the ASTM F2622 standard test method. No gas permeability was observed. This indicates that a non-porous solid membrane with a small number of closed pores has been obtained.

[0072] Example 2 All steps are similar to those in Example 1, except that during the fibrillation process, only PPS powder and PTFE powder are mixed at a weight percentage of 94%:6%, i.e., no cellulose fibers are present.

[0073] It has been shown that it is difficult to prepare films with a thickness of 1.0 mm to 1.5 mm using the first step of the film-forming process in Example 1. In this regard, it may be useful to perform several rounds of pre-compaction via a feeding mechanism to produce thick strips or ribbons.

[0074] The measured lithium-ion conductivity is 2.1 × 10⁻⁶. -4 S / cm 2 The tensile strength is 14.1 MPa.

[0075] Example 3 All steps are similar to those in Example 1, except that there is no PE layer lamination step in this example, and the final product consists only of a PPSCC self-supporting film without a PE laminate. The PPSCC film has a tensile strength of 5.1 MPa, which is much lower than the 19.1 MPa tensile strength of the multilayer structure. This demonstrates the influence of the third and second layers on the tensile strength of the multilayer structure.

[0076] Example 4 All steps are similar to those in Example 2, except that no PE layer is laminated in this example, resulting in a final product consisting only of a self-supporting PPS film without a PE laminate or cellulose nanofibers. The self-supporting PPS film, lacking cellulose nanofibers and a PE laminate, has a tensile strength of 0.4 MPa, significantly lower than in the previous example, making the winding of the thin PPS film very difficult.

[0077] Example 5 All steps are similar to those in Example 2, except that: The resulting 520 μm thick film was subjected to hot horizontal calendering controlled by constant force. Average film thicknesses of 7, 11, and 19 μm were obtained at a roll pressure of 30 kN (instead of 45 kN in Example 2), 130°C, 10% friction, and speeds of 0.5, 1.5, and 2.5 m / min, respectively, demonstrating the effect of roll pressure and speed on the final thickness of the PPS film.

[0078] Example 6 All steps are similar to those in Example 2, except for the following: The resulting 520 μm film was subjected to hot horizontal calendering, which was controlled by a constant gap, in contrast to the constant force in the previous embodiment. A PPS film thickness of 40-50 μm was obtained at a roll gap of 10 μm, a speed of 0.5 m / min, 10% friction, and a roll surface temperature of 130°C. This demonstrates that it may be difficult to make the final PPS film thin enough if controlled by a constant gap instead of force.

[0079] Example 7 All steps are similar to those in Example 1, except in this embodiment: Powder is fed into a powder roll precompactor via a feeding mechanism to prepare thick strips / belts, which are then fed directly at 50°C into multiple consecutive vertically automatic gap-controlled rollers, as described in Example 1, to produce a film with a thickness of 1.0 to 1.5 mm.

[0080] Pinholes were observed in the last 15 μm after hot pressing, demonstrating the importance of pre-compaction at room temperature.

[0081] Example 8 All steps are similar to those in Example 1, except that the PPS powder is pre-sodiumized in this embodiment: The procedure is similar to step 2 of Example 1, except that in this embodiment, polyphenylene sulfide powder containing 600 ppm Na, cellulose fibers, and PTFE powder are mixed in a weight percentage of 91%:3%:6%. The measured porosity is 9%. The pores are filled with NaBF4 electrolyte, and the measured Na ion conductivity is 1 × 10⁻⁶. -4 S / cm 2 .

[0082] Example 9 All steps are similar to those in Example 1, except that in this example, the fibrillation process is used to manufacture the separator for the Zn battery: The procedure is similar to step 2 of Example 1, except that in this embodiment, the pre-zincified polyphenylene sulfide powder, cellulose fibers, and PTFE powder are mixed in a weight percentage of 91%:3%:6%. The measured porosity is 6%. The pores were filled with 1M Zn(CF3SO3)2 electrolyte, and the measured Zn ionic conductivity was 5 × 10⁻⁶. -3 S / cm -1 Those skilled in the art will understand that the accompanying drawings are merely illustrative. The relative proportions of the various elements may also be distorted.

[0083] It should be noted that the above embodiments are illustrative rather than limiting of the invention, and those skilled in the art will be able to devise many alternative embodiments without departing from the scope of the appended claims. Any reference numerals placed between parentheses in the claims should not be construed as limiting the claims. The use of the verb "comprising" and its variations does not exclude the presence of elements or steps other than those described in the claims. The article "a" or "an" preceding an element does not exclude the presence of a plurality of such elements.

[0084] The mere fact that certain measures are described in mutually different dependent claims does not indicate that combinations of these measures cannot be used advantageously.

Claims

1. A solid separator for a battery, the solid separator comprising: - The first layer comprises a pre-lithiated or pre-sodium-lithiated polyphenylene sulfide (PPS) cellulose nanofiber (CelNF) composite self-supporting membrane; - The second layer comprises a porous polyolefin membrane; and, - The third layer includes a ceramic nanolayer disposed between the first and second layers.

2. The solid-state battery separator according to claim 1, wherein, The second layer comprises polyethylene (PE) and / or polypropylene (PP).

3. The solid-state battery separator according to claim 1 or 2, wherein, The thickness of the second layer is 3-15 μm, preferably 5-10 μm.

4. The solid separator according to any one of the preceding claims, wherein, The first layer comprises PPS, CelNF and polytetrafluoroethylene (PTFE) powder, with a weight ratio of 89-97%:0.1-5%:3-8%, preferably 90-94%:1-3%:4-6%.

5. The solid separator according to any one of the preceding claims, wherein, The thickness of the ceramic nanolayer is 30-300 nm.

6. The solid-state battery separator according to any one of the preceding claims, wherein, The thickness of the first layer is 5-45 μm, preferably 10-30 μm, and even more preferably 15-25 μm.

7. The solid-state battery separator according to any one of the preceding claims, wherein, The porosity of the first layer is less than 10%, preferably less than 3%.

8. The solid-state battery separator according to any one of the preceding claims, wherein, The third layer includes one or more of the following: - Aluminum oxide; -Li-rich ceramics, such as Li salts, Li-rich cathode materials, lithium phosphorus oxynitride (LiPON), or lithium titanate; - Highly porous materials, such as carbon nanospheres or metal-organic framework (MOF) materials.

9. The solid separator according to any one of the preceding claims, wherein, The thickness of the diaphragm is 10-60 μm, preferably 15-30 μm, and even more preferably 20-25 μm.

10. The solid separator according to any one of the preceding claims, wherein, The width of the solid diaphragm is 5-160cm.

11. A solid-state battery comprising a solid separator according to any one of the preceding claims.

12. The solid-state battery according to claim 11, wherein, The solid-state battery is a Li-ion battery or a Na-ion battery.

13. A method for preparing a self-supporting pre-lithiated or pre-sodium-treated polyphenylene sulfide (PPS) cellulose nanofiber composite membrane, the method comprising the following steps: - The metal chloride, tetrachloro-p-benzoquinone (TCBQ), and PPS powder dissolved in deionized water (DIW) are mixed and ground to form a mixed slurry; - Transfer the mixed slurry to a reactor for hydrothermal treatment; - The mixture after hydrothermal treatment is washed and filtered in a centrifuge; - The filtered solution is dried to decompose the PPS powder; - The decomposed PPS powder is mixed with cellulose fiber and polytetrafluoroethylene (PTFE) powder at a temperature when the PTFE powder is in a glassy state to obtain a mixed solution; - The mixture is ground in dry compressed air; - The milled mixture is compacted using one or more rollers to obtain a film; as well as, - Pass the membrane through a hot calender to obtain a self-supporting pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite membrane.

14. A method for preparing a self-supporting, pre-lithiated or pre-sodium-treated polyphenylene sulfide (PPS) cellulose nanofiber composite membrane, the method comprising the following steps: - The metal chlorides, tetrachloro-p-benzoquinone (TCBQ), PPS powder and cellulose fibers dissolved in deionized water (DIW) are mixed and ground to form a mixed slurry; - Transfer the mixed slurry to a reactor for hydrothermal treatment; - The mixture obtained from hydrothermal treatment is washed and filtered in a centrifuge; - The filtered solution is dried to decompose the PPS powder; - The decomposed PPS powder is mixed with polytetrafluoroethylene (PTFE) powder at a temperature when the PTFE powder is in a glassy state to obtain a mixed solution; - The mixture is ground in dry compressed air; - The milled mixture is compacted using one or more rollers to obtain a film; - Pass the membrane through a hot calender to obtain a self-supporting pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite membrane.

15. The method according to claim 13 or 14, wherein, The metal chloride is one or more of the following: - Lithium chloride; - Sodium chloride; -Magnesium chloride; and, - Aluminum chloride.

16. The method according to any one of claims 13-15, wherein, The PPS powder is a semi-crystalline PPS powder with linear chains and terminal crosslinking, and its crystallinity is >60% in the range of 1-25 μm, preferably 1-5 μm.

17. The method according to any one of claims 13-16, wherein, The mass ratio of the metal chloride, DIW, and TCBQ to the total mass of PPS is approximately 1:30:5:

100.

18. The method according to any one of claims 13-17, wherein, The hydrothermal treatment was carried out for 2 hours at a reaction temperature of approximately 210°C and a vapor pressure of 60-70 bar.

19. The method according to any one of claims 13-18, wherein, The mixing of PPS powder with cellulose fibers and PTFE is carried out at a temperature of 45-50°C.

20. The method according to any one of claims 13-19, wherein, The grinding is carried out in an air jet mill, which is preheated to a temperature of 40-50°C by compressed air.

21. The method according to any one of claims 13-20, wherein, The step of compacting the ground mixture using one or more rollers includes producing a film with a thickness of 1.0-3.0 mm, preferably 1.0-1.5 mm.

22. The method according to any one of claims 13-21, wherein, Before passing the film through the hot calender, the method includes the step of cold rolling the film at a roll temperature of 40-70°, preferably 45-55°, to obtain a film with a thickness of 0.3-0.5 mm.

23. The method according to any one of claims 13-22, wherein, The roller temperature of the hot calender is 120-140℃, preferably 1250-130℃.

24. The method according to claim 23, wherein, The friction in the rollers of the calender is controlled at 1-20%, preferably 8-12%; the linear load is 500-250 N / mm, preferably 350-370 N / mm.

25. A method for preparing a solid-state separator for a battery, the method comprising preparing a self-supporting, pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite membrane according to any one of claims 12-24, the method further comprising the following steps: - A porous polyolefin membrane is laminated onto a PPS cellulose nanofiber membrane using an adhesive containing a ceramic nanolayer.

26. A system for carrying out the method of claim 25, the system comprising: - Main storage tank for metal chlorides, deionized water, tetrachloro-p-benzoquinone (TCBQ), PPS powder and optional cellulose fibers; - A mixer for mixing the contents from the main storage tank into a mixed slurry; - A reactor for hydrothermal treatment of the mixed slurry; - Centrifuges are used for washing and filtering slurries after hydrothermal treatment; - An apparatus for drying the filtered solution to decompose PPS powder; A secondary storage tank for the decomposition of PPS powder, polytetrafluoroethylene (PTFE) powder, and optional cellulose nanofibers (if not part of the main storage tank). - A mixer for mixing the contents from the secondary storage tank; - A grinder, used to grind a mixed solution in compressed air; - One or more pairs of rollers are used to compact the grinding solution into a film; - A hot calender, through which the compacted film is passed to obtain a pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite film; and optionally, - A laminator is used to add porous polyolefin membranes to self-supporting pre-lithiated or pre-sodiumized polyphenylene sulfide (PPS) cellulose nanofiber composite membranes via ceramic nanolayer adhesives to obtain solid-state battery separators.

Citation Information

Patent Citations

  • Pre-lithiated polyphenylene sulfide, polyphenylene sulfide-based solid electrolyte membrane, battery electrode sheet, quasi-solid-state lithium ion battery and method for manufacturing same

    US20220037696A1